Pola Guru dan Orang Tua Dalam Mengoptimalkan Minat Baca Siswa Kelas Rendah di Sekolah Dasar - Murtianingsih, Febriana; Fathoni, Achmad (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2024)
This study aims to describe the pattern of teachers and parents to optimize the reading interest of lower grade students in elementary schools. This study uses a qualitative method with a descriptive approach. The research was conducted at SD Negeri Bulukantil Surakarta. Data collection techniques in this study were observation, interviews, and documentation. The subjects needed in this study were students, class teachers and parents of grade 1 students. The data analysis technique used was Milles and Huberman which consisted of data reduction, data presentation and conclusion drawing. The validity of the data used is triangulation of source data. The results of this study indicate that the pattern of teachers and parents has an important influence in optimizing the reading interest of lower grade students.